Halal brand awareness influence on consumers’ loyalty towards Islamic banking system - Maulan, Suharni; Omar, Nor Asiah (2015)

(untitled)
Majority of consumers are still unable to distinguish between Islamic and conventional banks despite their awareness of the Islamic banking existence. In a competitive market structure, brand awareness helps to create a basis of trust and acceptance. Brand awareness is the first step to create brand equity, an asset that provides companies with sustainable competitive advantages. This concern is critical to be addressed particularly in a dual banking environment such as in Malaysia, where consumers have choices between the Islamic and the conventional banking system. Accordingly, this paper aims to investigate the influence of halal brand awareness on consumers’ loyalty towards Islamic banking system. The model also includes brand loyalty as it is the core asset of brand equity. Using survey method, a data of 454 respondents have been analyzed using PLS-SEM. Interestingly, the findings shows that halal brand awareness shows greater influence than brand loyalty on consumers’ loyalty towards Islamic banking system. Thus, Islamic banks’ managers must operationalize effective marketing communication strategies by promoting the Islamic banking products with simplicity so as to facilitate greater consumers’ understanding. Its significance is not merely for organizational competitiveness, but more importantly is to ensure that in the long run the Islamic banking industry remains resilient.